Notes on the Alluring Weirdness of (Materialist) Rumination and Regurgitation: Reading Ariana Reines and Jamie Stewart - Henderson, Marius (Spaces and Fictions of the Weird and the Fantastic, 2019)
Marius Henderson’s chapter discusses rumination and regurgitation as modes of the figurative and literal, conceptual and embodied reprocessing of materials, which works with, through, and occasionally against plain juxtaposition. Taking Ariana Reines’s poetry collection The Cow (2006) as well as specific aspects of the sonic and lyrical works of Jamie Stewart/Xiu Xiu as touchstones, this chapter scrutinizes connections between weird politico-aesthetic practices of rumination and regurgitation and contemporary materialist theories. Via material-semiotic figurations—such as “the cow,” as an index of feminized ruminating guts in Reines’s poetry or the evocation of “self-abolition” in Stewart’s works—the artistic practices of Reines and Stewart reprocess the weirdness of their form and render palpable the violent structural formations that undergird it.
CRIS-Team Scopus Importer:2024-12-16